Renaissance Politics and Culture
1 online resource.
Keywords: Renaissance Politics and Culture collects ten essays by eminent scholars in Renaissance studies to celebrate the life and work of Robert Black, who has made some of the most original and significant contributions to the history of the Renaissance. Reflecting his interdisciplinary interests and approaches, these essays analyze education, humanism, political thought, printing, and the visual arts during this key period in their development. Contributors: James R. Banker, Jérémie Barthas, Davide Baldi Bellini, Jane Black, Lorenz Böninger, Jonathan Davies, James Hankins, John Monfasani, John M. Najemy, and Brian Richardson.